(untitled) - Wheelwright, Steven C. (New York,Toronto, 1992)
This book, written in 1992, started a whole revolution in looking at the management of product development. Concepts like: the funnel to focus the organization on the right projects, an aggregate project plan, and the best two pages on project management that I have ever read are in this book
Keywords: New products,Product management